MicroRNAs: small molecules, big effects. Issue 1 (February 2021) - Tinel, Claire; Lamarthée, Baptiste; Anglicheau, Dany
Abstract : Purpose of review: In kidney transplantation, microRNAs (miRNAs) have been extensively studied over the past decade, and panels of differentially expressed miRNAs have been identified from various body fluids/tissues, including blood, plasma, urine, or allograft biopsies, and in various conditions, such as acute T-cell-mediated and antibody-mediated rejections, chronic allograft rejection, interstitial fibrosis and tubular atrophy, acute tubular necrosis or BKV nephropathy. Recent findings: This review outlines our current knowledge regarding the complexity of miRNA regulation in fine-tuning expression of two-thirds of the human genome and the potential of miRNAs as biomarkers, based on an increasing number of case–control studies with, however, no evidence of short-term clinical development. Instead, a progressive change in study objectives is reported, with the most recent literature using miRNA-targeted genes as entry points for studying disease pathways. Summary: Our nascent understanding of their presumed roles in alloimmunity suggests that miRNAs are key regulators in many allograft injuries. Future directions should investigate how the integration of miRNAs with other layers of molecular data, such as genomic, transcriptomic, or proteomic data, could help to characterize the cellular interactions involved in allograft rejection and whether miRNA-based therapy could be of relevance for transplant medicine.